(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
A 6-week experiment was conducted to evaluate the growth performance and economic analysis of broad breasted bronze turkey growers fed diets containing fermented shea butter cake meal (FSBCM) as replacement for maize with Fullzyme® supplementation. Three treatment diets were formulated, where T1 contained maize-soybean based control diet, T2 had 25% FSBCM replacing maize in T1 diet and T3 contained 0.5% Fullzyme supplementation to T2 diet. A total of 72, six-week old unsexed broad breasted bronze turkey growers were weighed and allocated to three dietary treatments with four replications of six birds each in a completely randomized design (CRD). Data collected on feed intake, body weight gain and feed:gain as well as cost indices were subjected to analysis of variance with the aid of SAS software package. Feed and water were provided ad libitum. Results showed that significant (P<0.05) higher weight gain and lower feed intake were recorded in turkeys fed control and T3 diets compared to those offered T2 diet. Feed:gain deceased (P<0.05) in turkeys fed control and T3 diets than those fed T2 diet. Cost analysis revealed that cost/kg gain was significantly (P<0.05) lower in turkeys fed T3 diet compared to those on control and T2 diets. Cost of feed consumed, cost of production and % feed cost were higher (P<0.05) in control group than T2 and T3 groups. In conclusion, FSBCM can replace maize in turkey growers diet up to 25% level with mixture of enzymes cocktail and probiotics (Fullzyme) supplementation without compromising growth performance at a lower feed cost/kg weight gain.